Assessment on the Operation Management of MCP Aircon Services: Basis for Proposed Development Plan: Vol. 5, No. 1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to determine the assessment of the operation management of MCP Aircon Services in terms of customer focus, process management, planning process, process improvement, and total participation.The study utilized descriptive correlational research which employed to ten (10) customers and ten (10) employees of MCP Aircon Services.From the result of the study, it reveals that the operation management of MCP Aircon Services development plan; the operation management evaluated as “Strongly Agree” in terms of customer focus, process management, planning process, process improvement and total participation; the problems encountered in terms of services in communication was poor; and there is proposed development plan of operation management.This study recommended that the company should consistently maintain the proposed “Development Plan in Operation Management” in MCP Aircon Services, and that the MCP Aircon Services should continue to implement total quality management such as customer focus, process management, planning process, process improvement and total participation. It is a must for a business to implement development plan factors to the employees such as rewards/tokens, manuals and checklist, make a development plan that assists/comply in improving their company especially in communication.
Keywords: Operation management; Aircon Services; Development plan